"Malu Apa Bossku?" Najib Razak's political rhetoric on facebook post 2018 general election / Mohamad Zamri Zainal Anuar and Nuurianti Jalli. - Zainal Anuar, Mohamad Zamri; Jalli, Nuurianti (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2020)
Social media have become one of the most important political tools in the modern world. In 2018, we witnessed the downfall of the Barisan Nasional (BN) government. After 61 years of governance, it fell to its long-term nemesis, Pakatan Harapan (PH). Though PH has been praised for mastering the online arts first, both political coalitions have actively utilised social media to disseminate political propaganda. Increased support of PH has been evident despite stringent control over traditional broadcast and printing press. After 2008, BN lost its political hegemony in the Malaysian parliament, eventually lost the majority seats and failed to form a government a decade later. This research focuses on the Facebook rhetoric of Najib Razak, former leader of BN, after his loss in the 14th Malaysian general election (GE14). While concentrating on the Semenyih by-election, the researchers also looked at the different propaganda techniques Najib Razak used throughout this period, based on the propaganda technique blueprint by the Institute for Propaganda Analysis (IPA). Content analysis of Najib Razak's Facebook updates from January 12, 2019, until March 1, 2019, revealed that the former prime minister had utilised five different dominant propaganda agendas against PH. It was also found that Najib Razak frequently used name-calling as a technique to create public discord against the new government.